Changing local politics in South Africa: the power relationship between local government and the people - Zaaiman, Johan; Heydenrych, Pieter (Faculty of Humanities, University of the Free State, 2013)
The South African Freedom Charter (1955) states that “The people shall govern” and the African National Congress (ANC) (1991) stated in “Advance to national democracy” that “the immediate issue on the agenda is the question of political power. To affect the transfer of power into the hands of the people as a whole is the most crucial and immediate challenge facing the national democratic movement.” The question now is how this power is currently exercised where the ANC is the government and represents the people. Dennis Wrong stated that “politics includes both a struggle for power and a struggle to limit, resist and escape from power”. This implies that power is reciprocal. In South African local politics this mutuality of power relations presents different appearances. This article explores whether local power is shifting from the liberation movement as government to the people (considering for example protest politics) and as such whether the power of local government and that of the citizens are necessarily oppositional; or whether the struggle for democracy came full circle and that power is being democratised in a true sense by the people themselves as “governors” of government.
Keywords: Power; Local government; Democracy; People; ANC; Government; Protest; South Africa